2013
DOI: 10.3389/fnsyn.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

The temporoammonic input to the hippocampal CA1 region displays distinctly different synaptic plasticity compared to the Schaffer collateral input in vivo: significance for synaptic information processing

Abstract: In terms of its sub-regional differentiation, the hippocampal CA1 region receives cortical information directly via the perforant (temporoammonic) path (pp-CA1 synapse) and indirectly via the tri-synaptic pathway where the last relay station is the Schaffer collateral-CA1 synapse (Sc-CA1 synapse). Research to date on pp-CA1 synapses has been conducted predominantly in vitro and never in awake animals, but these studies hint that information processing at this synapse might be distinct to processing at the Sc-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 70 publications
(119 reference statements)
3
30
0
Order By: Relevance
“…JAK-STAT signaling is linked to learning and memory as inhibition of JAK causes memory deficits in health (15) and in Alzheimer's disease (AD) models (16). The JAK-STAT pathway is pivotal for NMDA-LTD at hippocampal SC-CA1 synapses (17); however, it is unclear whether JAK-STAT signaling is involved in activity-dependent synaptic plasticity mechanisms at hippocampal TA-CA1 synapses, which exhibit distinct forms of plasticity (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…JAK-STAT signaling is linked to learning and memory as inhibition of JAK causes memory deficits in health (15) and in Alzheimer's disease (AD) models (16). The JAK-STAT pathway is pivotal for NMDA-LTD at hippocampal SC-CA1 synapses (17); however, it is unclear whether JAK-STAT signaling is involved in activity-dependent synaptic plasticity mechanisms at hippocampal TA-CA1 synapses, which exhibit distinct forms of plasticity (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…On the basis of recent establishment of in vivo perforant pathway LTP recording (Aksoy‐Aksel & Manahan‐Vaughan, ; Gonzalez, Villarreal, Morales, & Derrick, ), the role of synaptic Zn 2+ in perforant pathway LTP was examined by our original approach, in which a recording electrode attached to a microdialysis probe was used and the recording region was locally perfused with Zn 2+ chelators in ACSF via the microdialysis probe. Perforant pathway LTP was not attenuated under perfusion with CaEDTA (10 mM), but attenuated under perfusion with ZnAF‐2DA (50 μM), suggesting that intracellular Zn 2+ signaling is required for perforant pathway LTP as well as Schaffer collateral LTP (Takeda et al, ) (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GluA2-lacking AMPA receptors are required for the maintenance, but not induction of HFS-induced LTP at juvenile TA-CA1 synapses [59]. Recent in vivo studies demonstrate that LTP that lasts in excess of 24 h can be evoked by tetanic stimulation in freely behaving rats [56,64]. Further investigation found that this form of in vivo LTP is dependent on NMDA receptor activation [64].…”
Section: Long Term Potentiation (Ltp) At Ta-ca1 Synapsesmentioning
confidence: 99%
“…The stratum radiatum contains the SC pathway which originates in the CA3 region and is the indirect input into the CA1 region. However, the temporoammonic (TA) input originates from layer III of the EC and directly innervates the stratum lacunosum-moleculare of the CA1 region [55,56]. These two inputs to CA1 neurons not only differ in receptor and ion channel composition but also in the mechanisms underlying activity-dependent synaptic plasticity evoked at these synapses [56].…”
Section: The Temporoammonic (Ta)-ca1 Synapsementioning
confidence: 99%
See 1 more Smart Citation